Clinical magnetoencephalography: Eloquent brain area, brainwaves augmentation and MEG-based brain network with coherence and power spectral density changes - Idris, Z. (Nova Science Publishers, Inc., 2023)
Magnetoencephalography (MEG) has numerous clinical and research applications, especially in the field of epilepsy and presurgical functional mapping of eloquent areas. Compared to other neuroimaging modalities, it has excellent temporal and good spatial resolution. There are various sophisticated analysis procedures that contine to be developed. Some of those techniques are routinely applied for uncovering the systematic and dynamic neural processes during the resting state, in task and in the higher order cognitive functions. Our purpose in writing this chapter is to demonstrate several interesting neurosurgical cases, where patients exhibited improvements in their brainwaves and connectivity after surgeries with state-of-the-art MEG brain mapping. The improvements were proven by their MEG recordings and contemporary analysis. Thus, our chapter on MEG study sheds light on the application of MEG and how the brain responds toward any deficit in its major functions. Â© 2023 Nova Science Publishers, Inc.. All rights reseverd.